Third- and further-line therapy in advanced non-small-cell lung cancer patients: an overview. (October 2014) - Genestreti, Giovenzio; Grossi, Francesco; Genova, Carlo; Burgio, Marco A; Bongiovanni, Alberto; Gavelli, Giampaolo; Bartolotti, Marco; Di Battista, Monica; Cavallo, Giovanna; Brandes, Alba A
ABSTRACT : Non-small-cell lung cancer (NSCLC) treatment has led to improved efficacy and compliance due to individual tailoring of the therapeutic options and the use of strategies based on both clinical characteristics and histological and biological features of the disease. In nonsquamous NSCLC, novel agents, such as pemetrexed and bevacizumab, have improved survival in the first-line setting. Maintenance therapy with pemetrexed and erlotinib resulted in improved progression-free survival compared with second-line therapy at disease progression. In the second-line setting, pemetrexed improves survival in nonsquamous NSCLC compared with docetaxel, and erlotinib has shown a survival benefit compared with best supportive care in patients who did not previously receive an EGF receptor inhibitor. Although the benefit of first- and second-line treatment over best supportive care alone has been firmly established, the role of further-line treatment remains controversial. This article summarizes the state-of-the-art treatments in this setting.